Fetal Ovarian Cyst Rupture Resulting in Transient Fetal Ascites - Ömer Kandemir; Sertaç Esin; Deniz Esinler; Bülent Yırcı; Serdar Yalvaç (Medical Network, 2016)
A 21-year-old gravida 1 para 0 woman was referred to our maternal-fetal medicine center due to a fetal intraabdominal cyst at 32 weeks of pregnancy. On the ultrasonography, lateral and superior to the bladder, there was a sharply circumscribed, thin walled anechoic cystic structure measuring 56x58 millimeter. Our presumed diagnosis was fetal ovarian cyst and we decided to aspirate the fluid and scheduled it on Monday. The family was informed about the situation and the procedure was postponed on Monday for family decision. However, on Monday, there was no cystic structure but surprisingly, severe spontaneous fetal ascites developed. On the follow-up, one week later, there was no intraabdominal fluid or cyst. At 38 weeks 2 days of pregnancy, the patient vaginally delivered a 3460 grams healthy female baby. Although it is rare, ovarian cyst should be in the differential diagnosis of fetal ascites especially when it is recent and transient.